Effect of Myofascial Release Therapy In Addition To K-Tape on Chronic Plantar Fasciitis: Pharmaceutical Science-Physiotherapy for better pain management - Tamil Nidhi Pk; Anandhan D; Arun B; Anantharaj K (International Journal of Life Science and Pharma Research, 2022)
Plantar fasciitis is one of the most common cause of heel pain. Injury to the plantar fascia results in loss of normally resilient in fascia. Fascia becomes stiffened and prone to re-injury, which resulting in a vicious cycle of persistent pain and inflammation. Though many therapies would produce better results, there was less exploration on fascial release therapy and k- tape. The purpose of the study is to identify the effect of MFR in addition to K-tape on chronic plantar fasciitis. This is a Quasi- experimental study with 48 participants. The ethical approval was obtained and the study was conducted in multiple physiotherapy centers in Namakkal district, Tamil Nadu. All the participants were selected based on selection criteria mainly those who fulfil any of the three from below, 1) Heel pain increases in the morning with first few steps following prolonged bed rest 2) Pain localized to the inferior heel 3) Pain decreases with activity such as walking or moving 4) Pain score is between 3—7 cms in 10 cm VAS. 24 participants in the experimental group receive myofascial release therapy along with k-tape for 6 weeks, 24 participants in the control group receive stretching along with k-tape for 6 weeks. The outcome measures used in this study are pain and foot function by numerical pain scale and foot function index respectively. Results were analyzed using SPSS 20.0, the results show that there were significant differences obtained between the myofascial release therapy with the k-tape group when compared to k- tape only group. There was a pain score of 10.82 ± 0.196 (p < 0.001) and foot function index score of 10.6 ± 3.85 (p < 0.001). This study concluded that the use of Myofascial release therapy with K-tape reduces pain scores and improves foot function in plantar fasciitis.